Implemeting a component-based tool for interactive synthesis of UML statechart diagrams - Koskinen, Johannes; Mäkinen, Erkki; Systä, Tarja (Acta Cybernetica, 2002)
The Unified Modeling Language (UML) has an indisputable role in objectoriented software development. It provides several diagram types viewing a system from different perspectives. Currently available systems have relatively modest tool support for comparing, merging, synthesizing, and slicing UML diagrams based on their semantical relationships. Minimally Adequate Synthesizer (MAS) is a tool that synthesizes UML statechart diagrams from sequence diagrams in an interactive manner. It follows Angluin's framework of minimally adequate teacher to infer the desired statechart diagram with the help of membership and equivalence queries. MAS can also synthesize sequence diagrams into an edited or manually constructed statechart diagram. In this paper we discuss problems related to a practical implementation of MAS and its integration with two existing tools (Nokia TED and Rational Rose) supporting UML-based modeling. We also discuss information exchange techniques that could be used to allow the usage of other CASE tools supporting UML.